2021
DOI: 10.1038/s41467-021-22072-9
|View full text |Cite
|
Sign up to set email alerts
|

N-protein presents early in blood, dried blood and saliva during asymptomatic and symptomatic SARS-CoV-2 infection

Abstract: The COVID-19 pandemic continues to have an unprecedented impact on societies and economies worldwide. There remains an ongoing need for high-performance SARS-CoV-2 tests which may be broadly deployed for infection monitoring. Here we report a highly sensitive single molecule array (Simoa) immunoassay in development for detection of SARS-CoV-2 nucleocapsid protein (N-protein) in venous and capillary blood and saliva. In all matrices in the studies conducted to date we observe >98% negative percent agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 35 publications
10
133
0
Order By: Relevance
“…Our results show a clear advantage of NPS as a specimen in combination with the probed antigen test. This is in concordance with other antigen test systems which, in general, have shown lower sensitivity compared to NPS [ 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One of the automated antigen tests previously evaluated for saliva samples is the Lumipulse G SARS-CoV-2 Ag assay, a chemiluminescent enzyme immunoassay which received the CE marking for qualitative and quantitative detection of the SARS-CoV-2 N antigen on both saliva and NPS samples.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results show a clear advantage of NPS as a specimen in combination with the probed antigen test. This is in concordance with other antigen test systems which, in general, have shown lower sensitivity compared to NPS [ 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One of the automated antigen tests previously evaluated for saliva samples is the Lumipulse G SARS-CoV-2 Ag assay, a chemiluminescent enzyme immunoassay which received the CE marking for qualitative and quantitative detection of the SARS-CoV-2 N antigen on both saliva and NPS samples.…”
Section: Discussionsupporting
confidence: 89%
“…Another automated antigen test evaluated for saliva is the Simoa SARS-CoV-2 N Protein Antigen Test, which is an EUA for the qualitative detection of the N antigen from SARS-CoV-2 in NPS specimens. PPA and NPA of this assay with molecular testing were 92.3% and 98.1% (N = 26) for days 1–7 [ 53 ]. Thus, compared to these two SARS-CoV-2 antigen assays, the Elecsys Anti-SARS-CoV-2 Antigen assay has a lower sensitivity but higher specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With several studies demonstrating the role that plasma viremia has on COVID-19, and its possible predictor of mortality [ 18 , 35 , 36 ], D Shan and team embarked on developing a sensitive direct antigen test to measure the viral NC protein for both dried blood Mitra microsamples and also saliva [ 37 ]. Comparing to nasopharyngeal PCR, their assays showed >90% PPA for SARS-CoV-2 positive patients, and >98% negative percent agreement, for all matrices within a week of a PCR+ test.…”
Section: Analysis Of Antibodies From Dried Mitra Samplesmentioning
confidence: 99%
“…The nucleocapsid protein (N-protein) of SARS-CoV-2 is a structural protein that oligomerizes to form a complex surrounding viral RNA, thus protecting it from the host cell environment. It is abundantly expressed within infected cells, where it facilitates viral RNA transcription, an essential step for viral replication Recently an ultrasensitive Simoa ® immunoassay has been described that robustly measures SARS-CoV-2 N-protein in venous blood, dried blood microsamples, and saliva [ 1 ]. This study measured N-protein in longitudinal blood samples of COVID-19 patients and demonstrated readily detectable viral antigen two weeks after initial positive PCR testing, with concentrations gradually decreasing, inversely correlated with anti-SARS-CoV2 adaptive immune response.…”
mentioning
confidence: 99%